Propensity of Using Different Media For Book Publicity Among Bangladeshi Authors (Social Science Review, 2025)
Human minds may betray but books are one of the oldest and most reliable mediums to preserve the image of a period, a civilisation and its earned knowledge. A book itself acts as a disseminator of information and ideas. But the book has also some publicists: authors, publishers, readers and other stakeholders who publicize books. Books are publicized worldwide by various means through diverse and different media; media includes word-of- mouth, traditional mass media, and newer dimension to human communication, social media. There have been several studies on book marketing in Bangladesh on publishers and booksellers; but there is no study to examine the propensity of using different media for book publicity among native authors, as explored in this study. In the light of three research questions, four related theories and on the basis of surveys and key informant interviews, this qualitative study investigates which medium Bangladeshi authors use most to publicize their books and what are the reasons behind it. The study reveals that two-thirds of the Bangladeshi authors think that social media is becoming an alternative to mass media for book publicity. The study also explored how traditional word- of-mouth is taking newer shape for book publicity.Social Science Review, Vol. 42(1), June 2025, pp. 129-146